Small rectangular parasitic plane as patch antenna ground plane for broadband WLAN application - Norra Shiella, Razali; Azremi, Abdullah Al Hadi; Soh, Ping Jack; Saidatul Norlyana, Azemi; Ibrahim, M.I. (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org